2020
DOI: 10.1016/j.imr.2020.100480
|View full text |Cite
|
Sign up to set email alerts
|

Could herbal medicine (Soshihotang) be a new treatment option for COVID-19?: a narrative review

Abstract: Background While the world struggles under the coronavirus disease 2019 (COVID-19) pandemic, a variety of antiviral agents and symptomatic treatments are being administered to patients and urgent clinical trials are underway. Under these circumstances, it is important to explore various possibilities for the treatment of COVID-19 including herbal medicines. Among various herbal medicines, Soshihotang (SSHT, Xiao Chai Hu Tang in Chinese) has been prescribed to treat vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
10
0
2
Order By: Relevance
“…Xiao Chai Hu Tang, the representative formula for treating shaoyang syndrome could perfectly improve the symptoms as alternating chills, fever and chest tightness. Additionally, several studies have found that Xiao Chai Hu Tang could exert an anti-infection effect against SARS-CoV-2 (Kwon et al, 2020;. Da Chai Hu Tang, a representative formula for yang ming and bowel excess syndrome, could remarkably improve the symptoms such as constipation and abdominal distention in the severe cases of COVID-19 (Chen et al, 2020), which could be explained by the interior-exterior relationship between Lung and Large Intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao Chai Hu Tang, the representative formula for treating shaoyang syndrome could perfectly improve the symptoms as alternating chills, fever and chest tightness. Additionally, several studies have found that Xiao Chai Hu Tang could exert an anti-infection effect against SARS-CoV-2 (Kwon et al, 2020;. Da Chai Hu Tang, a representative formula for yang ming and bowel excess syndrome, could remarkably improve the symptoms such as constipation and abdominal distention in the severe cases of COVID-19 (Chen et al, 2020), which could be explained by the interior-exterior relationship between Lung and Large Intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Makino, Glycyrrhiza glabra L., Zingiber officinale Roscoe, and Ziziphus jujuba Mill. and has anti-infective and antiviral effects [ 10 , 11 ]. Besides, XCH is a basic formula in Qing-Fei-Pai-Du decoction used for treating COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A need for effective vaccine is being seen an as good preventive strategy in this pandemic [3]. So, a variety of antiviral agents and symptomatic treatments are being administered to patients and urgent clinical trials are underway, thus under these circumstances, it is important to explore various possibilities for the treatment of COVID-19 including herbal medicines [13]. Clarification transmission routes and pathogenic mechanisms, and identification of potential drug treatment targets will promote the development of effective prevention and treatment measures [14].…”
Section: Introductionmentioning
confidence: 99%